Urban ecology and global climate change - Singh, Pardeep; Tripathi, Sachchidanand; Bhadouria, Rahul 1982-; Upadhyay, Shweta 1987- (Wiley, 2022)
"Humankind is facing three major challenges viz. human overpopulation, urbanisation, and climate change with the onset of the twenty-first century (Steiner 2014). Presently, about seven billion (expected to reach 8.2 and 9 billion by 2025 and 2050, respectively) people are inhabiting the Earth which is more than any previous time. Urban areas and people living in the cities are increasing rapidly in size, globally (Mitchell et al. 2018). Over half (~54%) of the world's population is residing in the urban areas which is expected to grow to 60 and 80% by the year 2030 and 2050, respectively (Lee 2011; Vasishth 2015). Urbanisation phenomenon can be seen occurring on all the continents (except Antarctica); however, rapid urbanisation is happening, particularly in the Asia and Sub-Saharan Africa (Yu et al. 2017). Rapid urbanisation is putting severe stress on the planet Earth resulting in changes in the ecosystems from the landscape to the global scales (Steiner 2014; Colding and Barthel 2017)"--